The Effect of Interpersonal Conflict Between Coworkers on Teachers’ Stress: Effective Conflict Management Strategies - Nifriza, Ifna; Rahmalia, Indah; Reswary, Dahayu Annora (International Journal of Educational Dynamics, 2024)
Conflict at school can be caused by conflicting demands, needs, drives, or desires. If conflicts can be resolved well, cooperative relationships will improve, and levels of trust and productivity will increase. Conflicts arise due to ineffective conflict management. Failure to manage conflict hinders the achievement of shared goals and disrupts the dynamics of interpersonal relationships. The research was carried out using a qualitative study method (Single Instrumental Case Study), which is a type of case research as an example to get an overview of problems and prevent individuals from improving their performance. By focusing on natural and naturalistic phenomena that exist in schools and carried out by observation in the field with strategies for Proper conflict management teachers' stress can be reduced and their ability to handle conflict at school can be improved. This can help create a more harmonious and productive school environment for all parties involved. Interpersonal conflicts between colleagues must be resolved quickly so as not to damage work relationships, affect mental well-being, and even hurt the quality of teaching. Conflict between co-workers in schools can hardly be avoided completely, but effective conflict management can help reduce the impact of stress arising from such conflict. Interpersonal conflict between co-workers can have a significant impact on teacher stress in the educational environment.